Women’s Participation in India’s Labour Market : Socio-Economic Determinants - Bednáriková, Nina; Proch, Dominik; Stuchlíková, Zuzana, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
India’s rapid economic expansion over the past three decades has unfolded alongside a persistent paradox: female labour force participation (FLFP) remains among the lowest globally and declined markedly through the 2000s and 2010s despite rising income and education. This thesis examines the socio-economic, cultural, and structural determinants underlying this trajectory. The findings show that FLFP is constrained on the supply side by rising household income, limited labour-market returns to education, restrictive gender norms, marriage and caregiving responsibilities, and reduced autonomy and mobility. On the demand side, mechanisation in agriculture, a shortage of suitable non-farm employment, occupational segregation, informality, and wage discrimination significantly narrow women’s job opportunities. A comparative analysis of Himachal Pradesh and Haryana demonstrates how differences in labour demand, human capital, social norms, and safety conditions generate divergent regional outcomes. Overall, the study highlights that India’s low FLFP stems from mutually reinforcing constraints and that expanding women’s economic participation is essential for inclusive and sustained development.
Vedoucí práce: Dominik Proch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses